An intervention account of the distribution of main clause phenomena: Evidence from ellipsis - Authier, J.-Marc; Haegeman, Liliane (IBERIA: An International Journal of Theoretical Linguistics, 2014)
Based on an examination of some asymmetries between VP ellipsis and VP fronting, this paper argues for an intervention approach and against a truncation approach to the distribution of main clause phenomena in adverbial clauses and, by extension, in non-root contexts in general. Adopting Authier’s (2011) treatment of VP ellipsis whereby the to-be-elided VP undergoes fronting in the computational component but fails to be spelled out at PF, these asymmetries follow from the fact that a fronted VP, being an intervener for wh-movement in adverbial clauses, triggers a PF crash unless ellipsis allows the derivation to converge via Bošković’s (2011) ‘rescue by PF deletion’ mechanism. This proposal entails that adverbial clauses are derived by wh-movement (Haegeman (2006) among others) and that the landing site for VP fronting is available in a non-root environment, two assumptions that militate against a truncation account of non-root clauses.